2020
DOI: 10.1155/2020/1654653
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Risk Factors for Mortality in a Cohort of Patients with Tuberculosis

Abstract: Identify the treatment effects and risk factors for mortality in patients with pulmonary tuberculosis receiving antituberculosis treatment under the Directly Observed Treatment Short-Course (DOTS) program to reduce the mortality rate of tuberculosis. A retrospective cohort analysis was conducted on the outcomes of antituberculosis treatment of 7,032 patients with tuberculosis in the DOTS program, in the Tuberculosis Management Information System from 2014 to 2017 in Tianjin, China. The Kaplan–Meier method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
3
8
1
2
Order By: Relevance
“…According to the result obtained from the multivariable Weibull–Gamma shared frailty model, the risk of death was higher in HIV-positive co-infected TB patients and was statistically associated with the time to death of TB patients during treatment. This finding is consistent with those of a study conducted in the southern region of Ethiopia [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the result obtained from the multivariable Weibull–Gamma shared frailty model, the risk of death was higher in HIV-positive co-infected TB patients and was statistically associated with the time to death of TB patients during treatment. This finding is consistent with those of a study conducted in the southern region of Ethiopia [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, a one year increase in the age of TB patients increased the risk of death by 2.2%. This result implies that the age of patients was directly associated with the mortality of TB patients [ 35 , 36 , 37 ]. Similarly, [ 38 ] showed that mortality due to TB was indirectly associated with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has identified age as a potential risk factor for TB survival, suggesting mortality increases by 5.9% with increasing yearly age. 3 The findings of our study further implied the “60–75” age group was a negative influencing factor for long-term survival (five-year survival) and the “75–90” age group was a negative influencing factor for medium/long-term survival (three/five-year survival). For these older age group, affected factors including lower immunity levels, more comorbidities, and delayed diagnosis, might explain the effect on survival time.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the literature has demonstrated that the success rate of retreated patients was lower than that of those initially treated, indicating that retreated PTB cases may have a longer treatment time. 3 Thus, for reasons like longer treatment periods, such beneficial effects may be weakened in the former, and no statistically significant benefits were found for the medium/long-term survival of PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation